1972
DOI: 10.1042/bj1270833
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial oxidation of N-methylisonicotinate, a photolytic product of Paraquat

Abstract: Two bacteria have been isolated that are capable of oxidizing N-methylisonicotinate, a photodegradation product of Paraquat (1.1'-dimethyl-4,4'-bipyridylium ion). N-Methylisonicotinate-grown cells of strain 4C1, a Gram-positive rod, oxidized 2-hydroxy-N-methylisonicotinate without lag. Cell-free extracts of these cells converted 2-hydroxyisonicotinate into 2,6-dihydroxyisonicotinate; the reaction did not require molecular oxygen. Maleamate was deamidated and maleate isomerized to fumarate by soluble enzyme sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The same result was reported by Naik et al [21]. Organisms capable of metabolizing the monoisomers have been isolated [8,9,11,13], and it appears that all three can be converted to diols and metabolized via the maleamate pathway. Picolinate (Zpyridinecarboxylic acid) is metabolized by Bacillus [26] and by a gram-negative rod [13] after hydroxylation first at position 6.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The same result was reported by Naik et al [21]. Organisms capable of metabolizing the monoisomers have been isolated [8,9,11,13], and it appears that all three can be converted to diols and metabolized via the maleamate pathway. Picolinate (Zpyridinecarboxylic acid) is metabolized by Bacillus [26] and by a gram-negative rod [13] after hydroxylation first at position 6.…”
Section: Discussionsupporting
confidence: 81%
“…It appears that the unsubstituted ring is cleaved without initial hydroxylation . Isonicotinic acid (Cpyridinecarboxylic acid) may also be metabolized without initial hydroxylation, or it may be converted t o a dihydroxy derivative prior t o ring fission [8]. All monohydroxypyridines and monopyridinecarboxylic acids can be converted t o diols prior to ring fission .…”
Section: Introductionmentioning
confidence: 99%
“…INA1, these facts do not necessarily contradict an involvement of citrazinate as a true intermediate (Kretzer & Andreesen, 1991). 2-Hydroxyisonicotinate and citrazinate were finally also shown to be intermediates in N-methylisonicotinate metabolism by the unidentified Gram-positive strain 4C 1 (Orpin et al, 1972). A further intermediate was maleamate.…”
Section: Degradation Of Isonicotinate By Mycobacterium Sp Inalmentioning
confidence: 83%
“…During a study of the microbial metabolism of the widely used bipyridinium herbicides, paraquat (1,1'dimethyl-4,4'-bipyridilium dichloride) and diquat (1, 1'-diethylene-2,2'-bipyridilium dibromide), microorganisms were isolated that would degrade the monohydroxylated pyridines. 2-Hydroxypyridine and 3-hydroxypyridine were hydroxylated by Achromobacter strains (Houghton & Cain, 1972) to pyridine-2,5-diol which was then degraded by the maleamate pathway (Cain et al, 1974), a route also used by Pseudomonas putida when grown on nicotinic acid (Behrman & Stanier, 1957) and by a pseudomonad growing at the expense of picolinamide (Orpin et al, 1972). 4-Hydroxypyridine, however, was degraded by an Agrobacterium sp.…”
mentioning
confidence: 99%
“…An alternative mechanism of hydroxylation is involved in the hydroxylation of many heterocyclic compounds, such as uracil (Hayaishi & Komberg, 1952), nicotinic acid (Hughes, 1955;Holcenberg & Stadtman, 1969;Hirschberg & Ensign, 1971a,b), nicotine (Hochstein & Dalton, 1967) or N-methylisonicotinic acid (Orpin et al, 1972). Studies with H21180 have shown that the 02 incorporated into these hydroxylated products is derived from water with NADP+, an artificial dye such as Methylene Blue, or a particulate electron-transport system linked to 02 being required as electron acceptor:…”
mentioning
confidence: 99%